2018
DOI: 10.1080/08958378.2018.1450462
|View full text |Cite
|
Sign up to set email alerts
|

Assessing electronic cigarette emissions: linking physico-chemical properties to product brand, e-liquid flavoring additives, operational voltage and user puffing patterns

Abstract: Users of electronic cigarettes (e-cigs) are exposed to particles and other gaseous pollutants. However, major knowledge gaps on the physico-chemical properties of such exposures and contradictory data in published literature prohibit health risk assessment. Here, the effects of product brand, type, e-liquid flavoring additives, operational voltage, and user puffing patterns on emissions were systematically assessed using a recently developed, versatile, e-cig exposure generation platform and state-of-the-art a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 65 publications
(91 reference statements)
1
61
0
Order By: Relevance
“…The total SD was estimated because it accounts for the SD within the groups as well as among the groups (Sharma 2006). For some studies, there were insufficient data to estimate the SD because only means were reported, with no estimation of variability around those point estimates (Beauval et al 2017;Dunbar et al 2018;Margham et al 2016;Palazzolo et al 2017;Song et al 2018;Williams et al 2013;Williams et al 2017;Zhao et al 2018). The study by Olmedo et al (2018) reported medians instead of means (SDs) in the original publication, but we calculated them directly from the original data.…”
Section: Metal/metalloid Data Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…The total SD was estimated because it accounts for the SD within the groups as well as among the groups (Sharma 2006). For some studies, there were insufficient data to estimate the SD because only means were reported, with no estimation of variability around those point estimates (Beauval et al 2017;Dunbar et al 2018;Margham et al 2016;Palazzolo et al 2017;Song et al 2018;Williams et al 2013;Williams et al 2017;Zhao et al 2018). The study by Olmedo et al (2018) reported medians instead of means (SDs) in the original publication, but we calculated them directly from the original data.…”
Section: Metal/metalloid Data Synthesismentioning
confidence: 99%
“…The study by Olmedo et al (2018) reported medians instead of means (SDs) in the original publication, but we calculated them directly from the original data. For the study that reported two aerosol size fractions of particulate matter (PM 0:1 and PM 0:1-2:5 ), we kept only the PM 0:1 , because it is likely inhaled deep into the lungs, and metals/metalloids were not detected in the PM 0:1-2:5 (Zhao et al 2018).…”
Section: Metal/metalloid Data Synthesismentioning
confidence: 99%
See 3 more Smart Citations